Object-Oriented Analysis of Frame 3D Textile Structures - Orlovsky B. V.; Manoilenko O. P.; Bezuhlyi D. M. (Журнал інженерних наук)
The article applied an object-oriented approach to analyze complex mechanical and technological objects based on an example of frame 3D textile structure development for objects from composite materials. Based on the research, the principle of global class inheritance of objects was analyzed and summarized using the object-oriented approach for the mechanical-technological structure of 3D fabrics using mechanical technology of sewing, weaving, knitting, and knitting productions. The design scheme of a generalized topology of object-oriented design for mechanical and technological systems of 3D fabrics of sewing, knitting, weaving, and weaving productions was developed. Methods and equipment for manufacturing mechanical-technological frame structures of 3D objects from textile materials were presented. Novel concepts of object = 3D micro-model, object = 2D mini-model, and object = 3D macro-model for frame 3D textile structures were introduced. Principles of inheritance, encapsulation, and polymorphism were applied to applicable models. For anisotropic textile 2D models, typical diagrams are given in polar coordinates for dynamic modulus of elasticity and logarithmic damping decrement.